Advanced controller design for speed control in a steam turbine coupled to DC generator - Hernando González-Acevedo; Hernan González-Acuña (Iteckne, 2018)
The paper presents the methodology for the design of two control strategies, LQG (Linear-Quadratic-Gaussian Control) and DMPC (Discrete Time Model Predictive Control), for speed control in a steam turbine coupled to separately excited DC generator. The dynamics of the system is represented by a linear model in which the model parameters are calculated using an optimization algorithm. The control strategies were implemented on a distributed control system (DCS), Delta V. The goal is to maintain the speed constant despite the variation of pressure in the steam pipeline and changes in the field resistance of the DC generator.